Pseudomonas aeruginosa is an Effective Indicator for Screening of Quorum Sensing Inhibition by Plant Extracts - Lafta, Inam Jasim; Sadeq, Zahraa (The Iraqi Journal of Veterinary Medicine, 2024)
Quorum sensing is a well-known mechanism used by many bacteria to control important virulence factors through the production and subsequent response to N-acylhomoserine lactones (AHLs). Quorum sensing inhibition (QSI), targeting AHL-dependent signalling, has been reported as a strategy for the control of bacterial pathogenicity. Thus, this study aimed at investigating the capability of Pseudomonas aeruginosa as an indicator to rapidly screen for potential QSI caused by plant extracts based on pigment inhibition. Four ethanolic plant extracts including: dried flower buds of clove (Syzygium aromaticum L), bark of cinnamon (Cinnamomum cassia L), leaves of moringa (Moringa oleifera Lam), and Al-Gutub (Tribulus terrestris L) dried fruits were investigated for their QSI ability in comparison with furanone (the known QS inhibitor). Agar well diffusion assay was used, in which the indicator isolate, P. aeruginosa, was inoculated onto Pseudomonas special agar medium containing 8 mm wells to load different concentrations of the plant extracts along with furanone or phosphate buffered saline (negative control). The results showed that furanone was successful in inhibiting the pyocyanin pigment of P. aeruginosa without interfering with the bacterial growth, this verified the ability of this bacterium as a potent QS indicator organism. Importantly, clove extract at different concentrations caused complete inhibition of the pyocyanin pigment with little impact on the bacterial growth. On the use of cinnamon, only the high concentrations showed clear dye inhibition of the indicator organism. Moringa also caused certain degree of dye inhibition but only at high concentrations. Conversely, Al-Gutub neither affected on the pyocyanin production nor on the bacterial viability. In conclusion, P. aeruginosa isolate, pyocyanin producer, was successful in the screening of QS inhibitors. This simple study recommends the use of such isolate without relying on the import of certain strains of Chromobacterium violaceum, Pseudomonas aureofaciens, or Agrobacterium tumefaciens‎‎‎‎‎.